آفاق تطوير العلاقات العراقية - الفرنسية - الجابري، ستار جبار (جامعة تكريت - كلية العلوم السياسية, 2016)
France is one of the most important countries for Iraq in the era prior to the US occupation of Iraq in 2003, but its position and position declined significantly after the occupation until recently, but French policy, especially under President Nicolas Sarkozy (2007-2012) adopted a different approach to his predecessors of French presidents , Especially his predecessor, Jacques Chirac (2002-2007), who distanced France from the Anglo-American war against Iraq in 2003, and Sarkozy took a new policy toward the United States. France is now trying to reap its benefits through the Iraqi gate, The tenth of February 2009, which is the first visit by a French president to Iraq since the founding of the Iraqi state, which was followed by the visit of President Francois Hollande (2012 - until now) in September 2014.
تعد فرنسا إحدى أهم الدول بالنسبة للعراق في الحقبة السابقة للاحتلال الأمريكي للعراق عام 2003، ولكن موقعها ومكانتها تراجعت بشكل كبير بعيد الاحتلال وحتى وقت قريب، ولكن السياسة الفرنسية، ولاسيما في عهد الرئيس نيكولا ساركوزي (2007-2012) اعتمدت نهجا مغايرا لأسلافه من الرؤساء الفرنسيين، ولاسيما سلفه جاك شيراك (2002-2007) الذي نأى بفرنسا كثيرا عن الحرب الأمريكية - البريطانية ضد العراق في العام 2003، واتخذ ساركوزي سياسة جديدة إزاء الولايات المتحدة، وفرنسا تحاول الآن أن تجني ثمارها عبر البوابة العراقية، وبالذات بعد الزيارة التاريخية للرئيس ساركوزي للعراق في العاشر من شباط 2009، والتي تعد أول زيارة لرئيس فرنسي للعراق منذ تأسيس الدولة العراقية، والتي أعقبتها زيارة الرئيس فرنسوا هولاند (2012- ولحد الآن) في أيلول 2014.
Keywords: الاحتلال الأمريكي للعراق -- العلاقات الفرنسية العراقية -- فرنسا -- العراق -- العلاقات السياسية